Impacts of Arctic warming and sea ice loss on the Northern Hemisphere mid-latitude large-scale circulation - Ronalds, Bryn, author; Barnes, Elizabeth A., advisor; Thompson, David, committee member; Randall, David A., committee member; Eykholt, Richard, committee member (Colorado State University. Libraries, 2020)
The consequences of the rapid warming of the Arctic and associated sea ice loss on the Northern Hemisphere atmospheric circulation is still largely debated. The uncertainty in the circulation response stems from a poor understanding of the underlying physical mechanisms of the remote response, regional and seasonal differences, differences between models and experimental set-ups, the large internal variability of the system, and the short observational record. This research seeks to address some of this uncertainty, specifically the uncertainty related to the physical mechanisms, regionality, and modeling differences. The wintertime Northern Hemisphere eddy-driven jet streams over the North Pacific and North Atlantic basins exhibit differing responses to Arctic warming and sea ice loss in a fully coupled climate model. In the North Atlantic the jet weakens, narrows along the poleward flank, and shifts slightly equatorward. This response is similar to previous studies examining the Northern Hemisphere zonal mean jet response. In contrast, the North Pacific jet strengthens and extends eastward in response to Arctic sea ice loss, with no change in latitude, and narrows slightly along the poleward flank. In both cases, there are high latitude anomalous easterlies in the region of sea ice loss, where the local surface temperature gradients are weakening. This can lead to changes in locations and frequency of wave-breaking, thus leading to changes in the mean zonal winds further south, in the vicinity of the jet. This work relates the differing changes in the North Pacific and North Atlantic to these changes in wave-breaking in a simplified atmospheric model, and posits that the location of the jet relative to the region of Arctic sea ice loss is a dominant factor in determining the mean jet response to the sea ice loss and local warming. Changes in the mean wintertime Northern Hemisphere midlatitude zonal winds are found to be indicative of changes to the sub-seasonal variability of the wintertime zonal winds. The sub-seasonal circulation patterns over the ocean basins are closely linked with continental weather regimes, including changes in temperature and precipitation. While establishing a causal link between Arctic sea ice loss and changes to remote weather regimes in the observational record remains difficult, the Polar Amplification Model Intercomparison Project (PAMIP) provides insight into possible relationships and consequences. The design of the project eliminates differences in experimental set-ups across models and aids in addressing the uncertainty in regional responses. Across four climate models, Arctic sea ice loss leads to a strengthened and extended North Pacific jet in the January-February mean. This mean change is also associated with changes to the sub-seasonal, wintertime North Pacific zonal wind variability. All four models show an increase in strengthened and extended North Pacific eddy-driven jet stream events and a decrease in weakened, retracted and equatorward-shifted North Pacific jet events in January-February. Previous work has also established the relationships between North Pacific jet stream variability and downstream, North American weather regimes, and changes to the former are expected to impact the latter. Again, there is model agreement in an increase of a warm west/cold east temperature dipole over North America, associated with the strengthened and extended jet events. There is also a decrease in cold air temperature anomalies over North America, associated with weakened and equatorward-shifted jet events.
Keywords: climate model; jet stream; simplified climate model; fluid dynamics; Arctic amplification; large-scale circulation